2016
DOI: 10.1002/oby.21692
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomic profiling of high‐fat diet‐induced obesity in mice: Importance of cytochrome P450‐derived fatty acid epoxides

Abstract: Objective: Enzymatic metabolism of polyunsaturated fatty acids leads to formation of bioactive lipid metabolites (LMs). Previous studies have shown that obesity leads to deregulation of LMs in adipose tissues. However, most previous studies have focused on a single or limited number of LMs, and few systematical analyses have been carried out. Methods: A LC-MS/MS-based lipidomics approach was used, which can analyze >100 LMs produced by cyclooxygenase, lipoxygenase, and cytochrome P450 (CYP) enzymes, to analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 39 publications
7
31
0
Order By: Relevance
“…2A) (11). GC-MS analysis showed that HFD treatment had no effect on the level of ARA or DHA in colon (SI Appendix, Table S3), and this result is in agreement with our previous study which showed that HFD had no impact on ARA levels in adipose tissues of HFD-treated mice (26). qRT-PCR showed that HFD increased expression of Ephx2 (encoding sEH) in colon tissues, while it had no effect on expression of Pla2g4a (encoding cytosolic calcium-dependent PLA 2 ) or CYP monooxygenases such as Cyp3a11, Cyp2c29, Cyp2c38, Cyp2c37, Cyp2c39, Cyp2j5, Cyp2j6, Cyp2j8, and Cyp2j9 ( Fig.…”
Section: Resultssupporting
confidence: 91%
“…2A) (11). GC-MS analysis showed that HFD treatment had no effect on the level of ARA or DHA in colon (SI Appendix, Table S3), and this result is in agreement with our previous study which showed that HFD had no impact on ARA levels in adipose tissues of HFD-treated mice (26). qRT-PCR showed that HFD increased expression of Ephx2 (encoding sEH) in colon tissues, while it had no effect on expression of Pla2g4a (encoding cytosolic calcium-dependent PLA 2 ) or CYP monooxygenases such as Cyp3a11, Cyp2c29, Cyp2c38, Cyp2c37, Cyp2c39, Cyp2j5, Cyp2j6, Cyp2j8, and Cyp2j9 ( Fig.…”
Section: Resultssupporting
confidence: 91%
“…The HFD + EY markedly lowered the content of neutral glycerolipid, such as TG and DG, in serum and FAs in liver compared with HFD. Hence, the inhibition of hepatic FAs and serum TG accumulation in HFD + EY is associated with the improvements in hyperlipidemia, which is consistent with previous studies …”
Section: Discussionsupporting
confidence: 92%
“…These results are largely in agreement with previous studies which showed that obesity induced a low-degree inflammation [37]. The profiles of LMs in adipose tissues and plasma in HFD-induced obesity are very different [10,35]. This is feasible, since most LMs are short-lived, locally produced and locally acting in response to cellular stimulation, followed with well-controlled degradation to maintain homeostasis [5,6].…”
Section: Discussionsupporting
confidence: 90%
“…It remains to determine the specific tissues and cell types involved in production of EpOMEs. It is not likely that the increased concentrations of EpOMEs in plasma are derived from adipose tissues, since studies by us and others have shown that there is a dramatic reduction of the expressions of CYP enzymes involved in biosynthesis of fatty acid epoxides, and reduced levels of CYP-derived fatty acid epoxides in adipose tissues of HFD-fed mice [10,35]. In our study, we also analyze the ratio of fatty acid epoxides to diols, which is a potential biomarker of sEH [5].…”
Section: Discussionmentioning
confidence: 99%